ANALISIS PENGARUH DIMENSI FRAUD DIAMOND TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA FAKULTAS EKONOMI (Studi Empiris Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Trisakti) - Anastasya Putri Yudiana; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2017)
This study aims to examine the factors that influence the behavior of academic fraud by students in the faculty of economics by using diamond fraud dimensions consisting of pressure, opportunity, rationalization and capabilities at the University of Trisakti environment. This study is using purposive sampling method and convenience sampling, purposive sampling is the selection of the sample taken not random, so that later on only samples that are necessary are to be tested, while convenience sampling means is easy with a qualititative approach that ultimately result in quantitative. The independent variables in this study is Fraud Diamond and the dependent variable is academic fraud by students in faculty of economics. Data was obtained through questionnaires with Likert scale. Statistical method in use is multiple linear regression with the help of SPSS 20 software. The results of this study indicate that students academic fraud behavior is influenced by the dimensions of the economic faculty of diamond fraud.